Diversity of axon initial segment geometry in the mouse hippocampus and its predicted influence on neuronal excitability - Stevens, Nikolas; Achilles, Maximilian; Monath, Juri; Langer, Rupert; Engelhardt, Maren; Both, Martin; Thome, Christian (Cerebral cortex, 2025)
Action potentials, the primary information units of the nervous system, are usually generated at the axon initial segment. Changes in the length and position of the axon initial segment are associated with alterations in neuronal excitability, but there is only limited information about the baseline structural variability of this compartment. This work provides a comprehensive analysis of the diversity of proximal cell geometries across all anatomical axes of the murine hippocampus, encompassing dorsal-ventral, superficial-deep, and proximal-distal regions. We analyzed the morphology of 3,681 hippocampal pyramidal neurons in 12 animals of both sexes, focusing on axon initial segment length, position, and association with proximal cellular features such as the soma and apical dendrite. Notably, neurons with axon-carrying dendrites were significantly more common in ventral compared to dorsal hippocampal areas, which we also found in two of three human samples. We employed NEURON simulations to assess the functional implications of this variability. Here, variation in proximal geometry contributed only minimally to neuronal homeostasis, but instead increased heterogeneity of response patterns across neurons.